Stop Bullying, Layanan Informasi Melalui Vidio Edukasi untuk Mencegah Perilaku Bullying pada anak Tpq/Tpa di Masjid Arroyhan Padangsidimpuan: Penelitian - Vitria Larseman Dela; Yulia Anita Siregar; Sahlan Tuah; Muhammad Darwis; Nurhasanah Pardede (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Peer groups are a primary source of reference for children regarding perceptions and attitudes related to lifestyle. As individuals mature and become adolescents, they begin to become familiar with a broader environment than their family. The socialization they experience increases. Individuals begin to interact with their peers. This bullying phenomenon can emerge in social interactions among peers, as both children and adolescents spend more time at school, making interactions with peers and teachers an integral part of their lives. The impact of bullying is psychological, including symptoms of depression, anxiety, fear, insecurity, restlessness, suicidal ideation, low self-esteem, increased isolation, drug abuse, and other health problems. Other impacts of bullying include feelings of fear and weakness that can affect their self-confidence. This situation can make adolescents who are victims of bullying unable to follow or pay attention properly in class. Based on the bullying phenomenon mentioned above, it is important to follow up.